Resistance to aztreonam-avibactam due to CTX-M-15 in the presence of penicillin-binding protein 3 with extra amino acids in Escherichia coli - Ma, Ke; Zong, Zhiyong (Frontiers in Microbiology, 2022)
Aztreonam-avibactam is a promising combination to treat carbapenem-resistant Enterobacterales including coverage for metallo-β-lactamases. Escherichia coli strains resistant to aztreonam-avibactam have emerged but resistance mechanisms remain to be elucidated. We performed a study to investigate the mechanism for aztreonam-avibactam in a carbapenem-resistant Escherichia coli clinical strain. This strain was highly resistant to aztreonam-avibactam (aztreonam MIC, 512 mg/L in the presence of 4 mg/L avibactam). Whole genome sequencing revealed that the strain carried metallo-β-lactamase gene blaNDM-4 and the extended-spectrum β-lactamase (ESBL) gene blaCTX-M-15 and had a YRIK four amino acid insertion in penicillin-binding protein 3 (PBP3). blaCTX-M-15 was cloned into pET-28a(+), followed by the transformation, with the gene, of E. coli strain 035125∆pCMY42 possessing the YRIK insertion in PBP3 and strain BL21 with the wildtype PBP3. blaCTX-M-14, another common ESBL gene, and blaCTX-M-199, a hybrid of blaCTX-M-14 and blaCTX-M-15 were also individually cloned into both E. coli strains for comparison. Aztreonam-avibactam resistance was only observed in the E. coli strains with the YRIK insertion in PBP3 that produced CTX-M-15 or its hybrid enzyme CTX-M-199. Checkerboard titration assays were performed to determine the synergistic effects between aztreonam-avibactam and ceftazidime or meropenem. Doubling avibactam concentration in vitro reversed aztreonam-avibactam resistance, while the combination of aztreonam-avibactam and ceftazidime or meropenem did not. In conclusion, CTX-M enzymes with activity against aztreonam, (e.g., CTX-M-15 and CTX-M-199), can confer resistance in the combination of PBP3 with YRIK insertions in metallo-β-lactamase-producing carbapenem-resistant E. coli. Doubling the concentration of avibactam may overcome such resistance.